Unsaturated soil mechanics for slope stabilization - Leong, Eng Choon (2011)
Rainfall-induced slope failures commonly occur in the unsaturated zone above groundwater table in many steep residual soil slopes. Dynamic variations in groundwater table and flux boundary conditions across ground surface result in changes in pore-water pressure in the unsaturated zone. During a prolonged dry period, excessive evaporation and evapo-transpiration on the ground surface causes soil desiccation and tension cracks to develop on the slope surface, increasing permeability of soils near the ground surface. In addition, the groundwater table can go down to deeper depths during the dry period. As a result, pore-water pressures in the unsaturated zone will become more negative, contributing to the shear strength of soil. During a rainy season, cracked soils with a higher permeability will increase rain infiltration into slopes and the groundwater table may rise, causing an increase in pore-water pressures in the zone above the groundwater table. As a result, the shear strength of the soil will decrease and factor of safety of the slope will be reduced to a low value that may trigger failures. Therefore, it is important to be able to protect unsaturated zone within a slope by controlling the groundwater level and the flux boundary conditions across slope surface as a slope stabilization method. One method of controlling groundwater level is using horizontal drains while the flux boundary conditions can be controlled using slope cover such as capillary barrier or vegetative cover. The mechanisms of these slope stabilization methods are based on principles of unsaturated soil mechanics since it is the unsaturated zone of the slope that needs to be maintained for the stability of the slope. In this paper, the mechanisms of unsaturated zone in a slope using several slope stabilization methods (i.e., horizontal drains, capillary barrier system and vegetative cover) are described using real field examples involving site investigation, installation, numerical analyses and instrumentation. The appropriateness and effectiveness of each slope stabilization method can be assessed using principles of unsaturated soil mechanics.